EZH2 mutations at diagnosis in follicular lymphoma: a promising biomarker to guide frontline treatment - C. Martínez-Laperche; L. Sanz-Villanueva; F. J. Díaz Crespo; P. Muñiz; R. Martín Rojas; D. Carbonell; M. Chicano; J. Suárez-González; J. Menárguez; M. Kwon; J. L. Diez Martín; I. Buño; et al. (BMC Cancer, 2022)
Abstract EZH2 is mutated in nearly 25% of follicular lymphoma (FL) cases. Little is known about how EZH2 affects patients’ response to therapy. In this context, the aim of this study was to retrospectively analyze the frequency of mutations in EZH2 at diagnosis in tissue and ctDNA in patients with FL and to assess the patients’ outcomes after receiving immunochemotherapy, depending on the EZH2 mutation status. Among the 154 patients included in the study, 27% had mutated EZH2 (46% with high-grade and 26% with low-grade FL). Of the mutated tissue samples, the mutation in ctDNA was identified in 44% of cases. EZH2 mutation in ctDNA was not identified in any patient unmutated in the tissue. Unmutated patients who received R-CHOP had significantly more relapses than patients who received R-Bendamustine (16/49 vs. 2/23, p = 0.040). Furthermore, our results show that patients with mutated EZH2 treated with R-CHOP vs. those treated with R-Bendamustine present a lower incidence of relapse (10% vs. 42% p = 0.09 at 4 years), a higher PFS (92% vs. 40% p = 0.039 at 4 years), and higher OS (100% vs. 78% p = 0.039 at 4 years). Based on these data, RCHOP could be a more suitable regimen for mutated patients, and R-bendamustine for unmutated patients. These findings could mean the first-time identification of a useful biomarker to guide upfront therapy in FL.